Situation of oral diseases of students at 2 secondary schools in Thai Binh City in 2020 (Vietnam Journal of Community Medicine, 2021)
A descriptive cross-sectional study on 424 students to assess the status of oral diseases of students at two secondary schools Ky Ba and Phu Xuan, Thai Binh city. The research results show that: The overall prevalence of dental disease (BRM) of the two schools is 53.8% (Phu Xuan: 70.9%; Ky Ba 41.8%, p
Keywords: Oral diseases, students of secondary schools.